Reliability of a new protocol to assess HR recovery after submaximal exercise - Romagnoli, M.; Alis, R.; Basterra, J.; Villar, J.; Perez, P.; Arduini, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
HR recovery after exercise is a measure used to assess adaptation to training and it has been proposed as independent predictor of all-cause mortality. The reliability of models for HR recovery assessment at submaximal intensities is poor and there a lack of standardization of the duration of recovery. It has been established that submaximal exercise is more reproducible than maximal and allows a better standardization of the test [1]. Our purpose is to determine the reliability of the indexes of HR recovery after a test on cycle ergometer at two submaximal exercise intensities (65% and 80% HRmax). Methods: HR recovery was assessed by 8 models, based on monoexponential kinetics or absolute recovery (recovered HR at fix time points) on 21 healthy subjects. Intraclass correlation coefficient (ICC) and standard error of measurement (SEM, %SEM) were used to address reliability of measurements. Results: Our results point to: assessment of HR recovery after 80% HRmax exercise is more reliable than after 65% HRmax (mean ICC: 0.827 vs. 0.747); at longer recovery time we found better absolute consistency of the measurement (%SEM: 26.7 at 60 s, 19.5 at 120 s and 16.3 at 180 s, irrespective of model or exercise intensity); to assess the fast component of HR recovery (HR kinetics calculated over . 60 s) after exercise T30min is more reliable than T30 (ICC: 0.691 vs. 0.528; %SEM: 28.5 vs. 70.8). Discussion: The protocol exhibits a good sensitivity of measurement - large ICC and small SEM . for analysis of HR recovery after submaximal exercise on cycle ergometer. Internal workloads of 80% HRmax has better reliability and the consistency of the results at this intensity increases with the duration of recovery.